The Thesaurus Theutonicae linguae (1573): dictionary as a grammar: Le Thesaurus Theutonicae linguae (1573) : dictionnaire comme grammaire - Zimont, Elizaveta (Revista do GEL, 2025)
Advocating for a more extensive use of dictionaries in the history of grammaticography, this case study focuses on the earliest alphabetical dictionary explicitly tailored to the needs of non-native speakers of Flemish. The Thesaurus Theutonicae linguae (1573), which predates by a decade the earliest known grammars of Flemish, contains numerous metalinguistic labels and comments dealing with Flemish grammar. Judging by the extent and the detail of metalinguistic information, this dictionary constitutes a remarkable step in the process of grammaticization of Flemish. While inspired by classical (Latin) framework, the metalinguistic analysis displayed in this work also benefits from the Renaissance interest in Greek and from emerging grammar writing in other vernaculars (French). Its foremost originality lies in the very first attempt to explain the functionning of separable complex verbs in Flemish, a grammatical feature that is alien to all three model languages (Latin, Greek, French).